Does vitamin D deficiency affect placental inflammation or infections among very low birth weight infants?. (18th July 2018) - Puthuraya, Subhash; Karnati, Sreenivas; Kazzi, S. Nadya J.; Qureshi, Faisal; Jacques, Suzanne M.; Thomas, Ronald
Abstract: Objective: Examine the association between placental inflammation and neonatal infections, and 25OH vitamin D (25OH D) levels at birth among very low birth weight infants (VLBWI). Study design: Serum 25OH D levels were measured in 89 VLBWI (≤1250 g) and 47 mothers on day one, and in 78 infants on day 21. Placentas were examined for maternal and fetal inflammation. Infants were divided into deficient (≤10 ng/ml) and adequate (>10 ng/ml) groups based on 25OH D levels on day 1. Results: Mean ± SD maternal levels of 25OH D (21 ± 9 ng/ml) correlated with infants' levels (15 ± 8 ng/ml), ( p < .001). 25OH D levels were lower in deficient (32/89) than in adequate group (8 ± 2 versus 20 ± 7 ng/ml, p = .011). Infants' 25OH D levels rose significantly by day 21 ( p < .001). Univariate analyses showed no differences between infant groups in maternal or fetal inflammation, or neonatal infections ( p > .05). Logistic regression analyses revealed no association between deficient 25OH D levels and the odds of maternal or fetal inflammation or other infections. Levels of 25OH D did not correlate with severity of placental inflammation. Conclusions: Deficient levels of 25OH D at birth are not associated with the occurrence of placental inflammation or neonatal infections among VLBWI.